Living yeast-based biostimulants: different genes for the same results? - Chambard, Marie; Albert, Benjamin; Cadiou, Mickaël; Auby, Sarah; Profizi, Camille; Boulogne, Isabelle (Frontiers in Plant Science, 2023)
Nowadays many products are available on the plant biostimulants market. Among them, living yeast-based biostimulants are also commercialized. Given the living aspect of these last products, the reproducibility of their effects should be investigated to ensure end-users’ confidence. Therefore, this study aimed to compare effects of a living yeast-based biostimulant between two different soybean cultures. These two cultures named C1 and C2 were conducted on the same variety and soil, but in different locations and dates until VC developmental stage (unifoliate leaves unrolled), with Bradyrhizobium japonicum (control and Bs condition) and with and without biostimulant coating seed treatment. The foliar transcriptomic analysis done firstly showed a high gene expression difference between the two cultures. Despite this first result, a secondary analysis seems to show that this biostimulant led to similar pathways enhancement in plants as well as with common genes or even if the expressed genes were different between the two cultures. The pathways which seem to be reproducibly impacted by this living yeast-based biostimulant are abiotic stress tolerance and cell wall/carbohydrate synthesis.